Análise proteômica e metabolômica dos fluidos do trato reprodutivo e células espermáticas de carneiros morada nova - Sousa, Solange Damasceno (2019)
The objective of the present study was to identify and characterize, through omics technologies (proteomics and metabolomics), the components present in the secretions of the genital tract and sperm cells of Morada Nova rams. In study 1, Fresh semen samples were collected from six adult rams (using an artificial vagina) and then obtained whole seminal plasma and ejaculated sperm. After, rams were vasectomized and fluid of accessory sex glands was collected (also using an artificial vagina). Next, animals were slaughtered and the epididymides, seminal vesicles and bulbourethral glands were properly collected for recovery of reproductive fluids and epididymal sperm. Two-dimensional electrophoresis, mass spectrometry and bioinformatics tools were used to map the major proteome of secretions from reproductive tract and sperm membranes. The most abundant proteins in the seminal plasma gels appeared as binder of sperm 1 (BSP1), binder of sperm 5 (BSP5), bodhesin-2 and spermadhesin Z13-like. Proteins from composite accessory sex gland fluid that contribute to seminal plasma composition include BSPs, bodhesins, 72kDa type IV collagenase, BPI fold-containing family A member 1, clusterin, inactive ribonuclease-like protein 9, inhibitor of carbonic anhydrase-like isoform X2 and albumin. Cauda epididymal fluid contributes to seminal plasma with specific proteins, such as epididymal-specific lipocalin-5-like isoform X1 and epididymal secretory protein E1, prostaglandin-H2 D-isomerase and spermadhesin-1-like. Comparing 2-D maps of membrane proteins from ejaculated and cauda epididymal sperm membranes, there is an increase in the intensity and number of spots in the ejaculated sperm maps. Those proteins are originated from accessory sex gland fluids. Further research into the proteins identified in our study can contribute to investigations of markers for sperm quality and fertility. In the study 2, five adult Morada Nova rams were vasectomized and accessory sex gland fluid (AGF) was collected by artificial vagina. Metabolites were extracted and identified by GC/MS and LC/MS. Metabolites obtained were analyzed by Human Metabolome Database (HMDB), PubChem, and LIPID Metabolites and Pathways Strategy databases. Pathway analysis was performed using MetaboAnalyst 3.0. Combined use of GC and LC/MS allowed the identification of 371 compounds from AGF of rams. These techniques presented an overlap of one single metabolite, thus confirming the complementarity of the approaches used. Lipids and lipid-like molecules were the most abundant classes in the ram AGF, followed by amino acids, peptides, and analogues. The most abundant metabolites were fructose, glycerol, citric acid, D-mannitol, D-glucose and L-(+)-lactic acid. Metabolites identified in the ram AGF were involved in 52 different pathways. AGF metabolites are modulators of sperm function, thus chemical analysis of the accessory sex gland fluid is valuable to better understand animal reproduction and to search for biomarkers of fertility.